Turning Against Object: The Aggressive Defence Style Adopted by Adolescents - Abraham, Mercy; George, Reena (INDIAN EDUCATIONAL REVIEW, 2007)
Aggression is a prime human characteristic necessary for survival in the struggle for existence. Aggression is often used as a defence against dangerous pleasures. The aggressive style of defence viz., ‘Turning Against Object’, adopted by adolescents in the age group of 13-17 years, is studied with respect to the age, gender and locale. The sample for the study constitute a representative group of 1730 adolescents in the age group of 13-17 years, studying in the Secondary and Higher Secondary schools of Kerala. ‘Adapted Version of the Defense Mechanisms Inventory’ was the tool used. Analysis of Variance (ANOVA), Scheffé Test for post hoc analysis and Critical Ratios were employed for data analysis. The study found that the adoption of ‘Turning Against Object’ decreases with age. Gender as well as Locale were found to have a significant influence on the adoption of ‘Turning Against Object’ as aggressive defence style among adolescents in the age group of 13-17 years.